ANALISIS PENDAPATAN INDUSTRI TAHU (Studi Kasus pada Industri Rumah Tangga Tahu “KALKID” di Desa Kalitinggar Kidul Kabupaten Purbalingga) - Ayu Sitanini (Institute of Computer Science (IOCS), 2023)
This study aims to identify the tofu processing industry in Kalitinggar Kidul village, Purbalingga district and determine the income level from the production of tofu